Draft Genome Sequence of Staphylococcus sciuri subsp. sciuri Strain Z8, Isolated from Human Skin - Hu, Xinjun (Genome Announc, 2015)
Staphylococcus sciuri subsp. sciuri strain Z8 was isolated from a skin wound infection of a patient with infective endocarditis. To the best of our knowledge, the genome sequence of the species S. sciuri has not been previously studied. The complete genome sequence of strain Z8 includes a genome of 2,620,868 bp (32.43% GC content) without any plasmids.